Venimus ad summum Fortunae: Prosperity and Flourishing of Arts in Horace (Epist. 2. 1. 32–33) - Keyer, Denis (Hyperboreus, 2015)
The explanations of the passage Hor. Epist. 2. 1. 32–33 that prevail in scholarly literature are not satisfactory, though the asyndeton in v. 32 is rightly taken as conclusivum and the distichon as a paralogism. The author defends at length the interpretation of L. Bösing (1972): the trace of thought suggests the implicit premise, which must have become a commonplace: ‘The wealth and peace in the 5th century Greece after the Persian Wars resulted in the ﬂourishing of arts’ (cf. v. 93–102, Aristot. Pol. 8. 6. 6. 1341 a 28–32, Diod. 12. 1. 4). This presumed analogy with Greece leads to the ironic analogical conclusion that, since Romans enjoy the highest possible degree of prosperity and wealth, they must not only equal Greeks in painting, music and wrestling, but even surpass them.